1.7. Digital Pompeii: Dissolving the Fieldwork-Library Research Divide - (:unkn) unknown (My University, 2016)
The advent of new forms of digital archaeological practice is revolutionizing the ways in which archaeologists work in the field. We have already witnessed the first part of the revolution, which has transformed archaeological methods of data collection and how such data are accessed and deployed in the field. In the second act of this revolution, published scholarship in digital form will be as easy to implement in the field as the trowel, effectively (if theoretically) dissolving the spatio-temporal division between fieldwork and library work. This paper describes two examples of this dissolution of the fieldwork-library divide, one archival in nature (Pompeii Quadriporticus Project) and the other bibliographic (Pompeii Bibliography and Mapping Project). The brief discussion of each sets the stage for a more speculative foray into how such digital practices will transform archaeological practice in the coming decade.
Keywords: Pompeii; library; fieldwork; excavation; digital methods